2005
DOI: 10.1103/physrevlett.95.224302
|View full text |Cite
|
Sign up to set email alerts
|

Supersonic Crack Propagation in a Class of Lattice Models of Mode III Brittle Fracture

Abstract: We study a lattice model for mode III crack propagation in brittle materials in a stripe geometry at constant applied stretching. Stiffening of the material at large deformation produces supersonic crack propagation. For large stretching the propagation is guided by well-developed soliton waves. For low stretching, the crack-tip velocity has a universal dependence on stretching that can be obtained using a simple geometrical argument.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…The most remarkable results we obtain are the following. For stiffening of the springs at large stretching we find an extensive supersonic branch similar to one previously found for mode III configurations (Guozden and Jagla 2005). We also show that in the absence of dissipation, the size of the anharmonic zone scales as the width of the system, i.e., it occupies always a finite fraction of the system width.…”
Section: Additional Elastic Nonlinearitiessupporting
confidence: 54%
See 3 more Smart Citations
“…The most remarkable results we obtain are the following. For stiffening of the springs at large stretching we find an extensive supersonic branch similar to one previously found for mode III configurations (Guozden and Jagla 2005). We also show that in the absence of dissipation, the size of the anharmonic zone scales as the width of the system, i.e., it occupies always a finite fraction of the system width.…”
Section: Additional Elastic Nonlinearitiessupporting
confidence: 54%
“…From this type of analysis we concluded that once cracks go supersonic the velocity is independent of L y . Moreover, additional considerations (see Guozden and Jagla 2005) suggested that the velocity is also largely independent of γ and δ/u bk ; i.e., it is determined by the value of δ/u nl alone.…”
Section: Fig 18mentioning
confidence: 98%
See 2 more Smart Citations
“…It has been recently established [7,8] that the propagation velocity in this kind of model crucially depends on the presence of anharmonicities of the springs. These anharmonicities are also called hyperelastic effects.…”
Section: Introductionmentioning
confidence: 99%